Comparative Analysis of Investment Policies in Indonesia and Vietnam: Challenges, Opportunities, and Strategic Insights for FDI Optimization - Yosif, Mohamed Alamin Ibrahim; Gibreel Musa Saleh, Husny; Rahimjon, Dilbarova Malika (JIAN (Jurnal Ilmiah Administrasi Negara), 2025)
This study explores the comparative strengths and challenges of Indonesia and Vietnam in attracting foreign direct investment (FDI). Employing a comprehensive literature review and a comparative policy analysis framework, the research examines key factors influencing investment, including tax policies, labor markets, infrastructure, regulatory environments, and environmental sustainability. Findings reveal Vietnam's competitive advantages in centralized governance, lower labor costs, and rapid adoption of renewable energy, supported by trade agreements such as the CPTPP. In contrast, Indonesia's opportunities lie in its vast natural resources, ambitious infrastructure projects, and potential for energy and digital economy growth, though hampered by bureaucratic inefficiencies and regional disparities. Both countries show commitment to green growth, but Vietnam's progress outpaces Indonesia's in renewable energy adoption. Recommendations include enhancing regulatory efficiency, promoting sustainable urban planning, and fostering ASEAN regional cooperation to attract and retain FDI. This study contributes novel insights into policy optimization, providing actionable strategies for policymakers and stakeholders to bolster economic growth in Southeast Asia.